Гепатит В Билан Ҳомиладор Аёлларда Инфекциянинг Вертикал Ўтишининг Профилактикаси - Фуркатовна, Амонова Мадина; Матлуба, Сатторова (Journal of Science in Medicine and Life, 2024)
The aim of the study was to conduct an analytical review of modern sources of scientific literature covering the screening and prevention of vertical transmission from mother with HBV to the child. Materials and methods. The analysis of 69 foreign sources of literature on this topic. Results. The review highlights the theoretical and practical issues of preventing vertical transmission of infection, describes the effectiveness of screening for this disease and the tactics of managing pregnancy in infected women. Conclusion. The high prevalence of hepatitis B during pregnancy makes it an urgent problem. The analysis shows that the active-passive immunization of newborns from HBeAg_positive mothers is an effective way to prevent neonatal transmission of hepatitis B. / ml recommended in the third trimester bere_chemoprophylaxis with lamivudine, tenofovir and telbivudine, among which tenofovir is preferred.